SUDEP: The Worst in Epilepsy and the Hardest to Image - Englot, Dario J. (Epilepsy currents, 2020)
Altered Brain Connectivity in Sudden Unexpected Death in Epilepsy (SUDEP) Revealed Using Resting-State fMRI Allen LA, Harper RM, Guye M, et al. Neuroimage Clin. 2019;24:102060. The circumstances surrounding sudden unexpected death in epilepsy (SUDEP) suggest autonomic or respiratory collapse, implying central failure of regulation or recovery. Characterization of the communication among brain areas mediating such processes may shed light on mechanisms and noninvasively indicate risk. We used rs-fMRI to examine network properties among brain structures in people with epilepsy who suffered SUDEP (n = 8) over an 8-year follow-up period, compared with matched high- and low-risk subjects (n = 16/group) who did not suffer SUDEP during that period and a group of healthy controls (n = 16). Network analysis was employed to explore connectivity within a “regulatory subnetwork” of brain regions involved in autonomic and respiratory regulation and over the whole brain. Modularity, the extent of network organization into separate modules, was significantly reduced in the regulatory subnetwork, and the whole-brain, in SUDEP and high-risk groups. Increased participation, a local measure of intermodular belonging, was evident in SUDEP and high-risk groups, particularly among thalamic structures. The medial prefrontal thalamus was increased in SUDEP compared with all other control groups, including high-risk group. Patterns of hub topology were similar in SUDEP and high-risk groups but were more extensive in low-risk patients who displayed greater hub prevalence and a radical reorganization of hubs in the subnetwork. Sudden unexpected death in epilepsy is associated with reduced functional organization among cortical and subcortical brain regions mediating autonomic and respiratory regulation. Living high-risk subjects demonstrated similar patterns, suggesting such network measures may provide prospective risk-indicating value, though a crucial difference between SUDEP and high-risk groups was altered connectivity of the medial thalamus in SUDEP, which was also elevated compared with all subgroups. Disturbed thalamic connectivity may reflect a potential noninvasive marker of elevated SUDEP risk.